2014
DOI: 10.1093/mp/sst142
|View full text |Cite
|
Sign up to set email alerts
|

PIF3 Is Involved in the Primary Root Growth Inhibition of Arabidopsis Induced by Nitric Oxide in the Light

Abstract: SUMMARYNitric oxide (NO) promotes the accumulation of PHYB and thus reduces PIF3. The activity of PIF3 was also regulated by RGL3. PIF3 may lie downstream of PHYB and RGL3, and regulate NO-induced root growth inhibition of Arabidopsis seedlings in light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…As light is essential for plant growth and development, many components in photobodies have been showed to involve in numerous other pathways regulated by different environmental cues like plant hormones, temperature, nitric oxide, and many stresses [185][186][187][188][189][190][191][192][193][194][195][196]. Phytochrome-interacting factors (PIFs), one small subset of basic helix-loop-helix (bHLH) transcription factors, act as a cellular hub to intersect different signaling pathways [197][198][199].…”
Section: Photobodiesmentioning
confidence: 99%
“…As light is essential for plant growth and development, many components in photobodies have been showed to involve in numerous other pathways regulated by different environmental cues like plant hormones, temperature, nitric oxide, and many stresses [185][186][187][188][189][190][191][192][193][194][195][196]. Phytochrome-interacting factors (PIFs), one small subset of basic helix-loop-helix (bHLH) transcription factors, act as a cellular hub to intersect different signaling pathways [197][198][199].…”
Section: Photobodiesmentioning
confidence: 99%
“…In seeds, NO stimulates germination both under normal and stress conditions (Zhang et al, 2011;He et al, 2014;Pires et al, 2016), favors overcoming dormancy (Wang et al, 2015;Ma et al, 2016), promotes elongation and formation of adventitious roots (Schlicht et al, 2013;Bai et al, 2014) and enhances desiccation tolerance of recalcitrant seeds (Bai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The protective of NO to recover the loss of seed viability and/or vigor role is based on its ability to regulate the level and toxicity of reactive oxygen species (ROS) (He et al, 2014). Application of exogenous NO in the form of SNP alleviates the adverse effects caused by heat, salt and drought stress, by decreasing hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) contents and modulating the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and guaiacol peroxidase (GPX) (Lin et al, 2013;Filippou et al, 2013;Amooaghaie et al, 2015;Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This process leading to the development of autotrophic metabolism requires the ability to light response. Light-dependent Arabidopsis seed germination is mediated by photoreceptors, mostly phytochromes (PHY), that perceive Red/Far-Red radiation (Sullivan and Deng 2003;Bai et al 2014). It was demonstrated that NO fumigation substituted red light effect in photoblastic seeds and stimulated deetiolation of Arabidopsis seedlings (Giba et al 1998;Beligni and Lamattina 2000).…”
Section: Introductionmentioning
confidence: 99%
“…NO involvement in photomorphogenesis positively affected DELLA protein accumulation and negatively affected expression of one of the GA signaling component Phytochrome-Interacting Factor (PIF) in Arabidopsis seedlings (Lozano-Juste and León 2011). PIF proteins, including PIF3 is known to interact with PHY, while DELLA proteins are involved in inhibition of hypocotyls growth by decrease of PIF transcription activity (Bai et al 2014 and citation therein). Thus, it suggests interplay of PHY, GA, and NO as NO inhibited primary root growth of Arabidopsis seedlings throughout a reduction of PIF3 expression (Bai et al 2014).…”
Section: Introductionmentioning
confidence: 99%